2022
DOI: 10.1002/pits.22730
|View full text |Cite
|
Sign up to set email alerts
|

Online self‐regulated learning and academic procrastination: A moderated mediation model

Abstract: Online learning has recently replaced traditional offline learning as the mainstream learning model for Chinese college students owing to the COVID-19 pandemic. This study examined the relationship between online self-regulated learning and academic procrastination among 1149 Chinese undergraduates who participated in online learning. The effects of online self-regulated learning on academic procrastination and whether it was mediated by attention control and moderated by peer support were investigated. Mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Attentional control is essential for on-time academic completion. Students with high attentional control are more adaptive to distractions and external stimuli, leading to reduced attentional bias to unrelated information in performing academic tasks (Ma et al, 2022). Alternatively, students with impaired attentional control might spend more time on distractions such as short-form videos, even if they intend to concentrate in academic tasks.…”
Section: The Mediating Role Of Attentional Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Attentional control is essential for on-time academic completion. Students with high attentional control are more adaptive to distractions and external stimuli, leading to reduced attentional bias to unrelated information in performing academic tasks (Ma et al, 2022). Alternatively, students with impaired attentional control might spend more time on distractions such as short-form videos, even if they intend to concentrate in academic tasks.…”
Section: The Mediating Role Of Attentional Controlmentioning
confidence: 99%
“…To be specific, academic procrastination is defined as the act of failing to complete academic tasks that should be done properly, often accompanied by emotions such as stress and anxiety (Caroline et al, 2010). However, academic procrastination is a common issue for college students, with some studies report incidence of academic procrastination as high as 70% (Cheng and Xie, 2021;Ma et al, 2022). Continuous academic procrastination not only hinders students' academic achievement (Bytamar et al, 2020), but also prevents them from effectively regulating emotions and experiencing fulfillment (Balkis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature has provided preliminary and important insights into the occurrence of procrastination in online learning environments. Many studies have found that motivational beliefs and learning strategy use are the major factors that are associated with students' unnecessary postponement of coursework in online classes (Dunn, 2014; Ma et al, 2022; Pelikan et al, 2021). However, the recent development in the theory has offered a new perspective on the incidence of procrastination.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the reasons behind academic procrastination. Individual variables such as self-regulation, self-efficacy, self-esteem, and fear of failure all influence academic procrastination ( Li, Gao & Xu, 2020 ; Ma et al, 2022 ; Wang et al, 2021 ; Zarrin, Gracia & Paixão, 2020 ) Meanwhile, negative emotional states, such as anxiety, depression, and worry are all positively associated with academic procrastination ( Gadosey et al, 2021 ; Rahimi & Vallerand, 2021 ). Furthermore, task-related demands (such as task was incomplete, vague, or ambiguous) also correlate to academic procrastination ( Wieland et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%